Reorientasi Pengelolaan l!mu Hukum - HS. Brodjo Sudjono (Fakultas Hukum Universitas Islam Indonesia, 2004)
As an emperical science, legal science aims to obtain factual knowledge from the reality which originates from the experince, and it does not originate from the apriory of logical coherence. Thus, it is able to perform theoretical statements whichare ready to beevaluated on the validity of process which occuredin there ality. To the interest of the development on thelegal science, thp unity of opinion on ontology and epestimoiogy is required to establis hedan exemplaras tlie new and sound quality of resolving the puzzle which can be applied in the management of legal science model.